LITERATURE REVIEW THE ROLE OF ACUPUNCTURE IN THE MANAGEMENT OF PERIPHERAL NEUROPATHY - Rosalyn, Elisha; Septadina, Indri Seta (International Journal of Islamic and Complementary Medicine, 2024)
Peripheral neuropathy (PN) is a condition characterized by damage to the peripheral nervous system, resulting in symptoms such as pain, numbness, and weakness in the hands and feet. The most common causes include diabetes, thyroid disorders, vitamin B12 deficiency, alcohol abuse, chemotherapy, and human immunodeficiency virus (HIV) infection. Despite the availability of various treatments, neurological disorders remain a significant therapeutic challenge. The therapeutic effects of acupuncture are attributed to several mechanisms, including stimulation of nerve fibers, restoration of blood flow, release of neurotransmitters and hormones, modulation of the autonomic nervous system, anti-inflammatory effects, and increased neuroplasticity. These mechanisms collectively contribute to the relief of symptoms associated with peripheral neuropathy. Evidence suggests that acupuncture is beneficial in treating peripheral neuropathy. Studies have shown that acupuncture can improve nerve conduction study parameters in sensory and motor nerves, reduce neuropathic pain, and improve overall nerve function. Certain acupuncture points such as ST-36, GB-34, SP-3, SP-8, and BI-56 have been identified as particularly effective in managing symptoms of peripheral neuropathy. Although more rigorous studies are needed to fully characterize the effects of acupuncture on peripheral neuropathy, the available evidence supports its use as a complementary therapy. Standardized acupuncture protocols that combine anatomical correlation with peripheral nerves and traditional approaches to neuropathic pain management appear to be effective. Further studies with larger sample sizes and randomized comparisons to sham acupuncture will help establish acupuncture as a guideline for treating peripheral neuropathy. This review outlines the potential of acupuncture as a complementary therapy in the management of peripheral neuropathy.